Factors that influence the intra-articular rupture pattern of the ACL graft following single-bundle reconstruction - van Eck, Carola F. (Springer-Verlag, 2011)
PURPOSES: The number of revision anterior cruciate ligament (ACL) surgeries performed annually continues to rise. The purpose of this study was to determine the most common rupture pattern in ACL revision cases after previous single-bundle reconstruction. The second aim was to determine the relationship between rupture pattern and patient-specific factors (age, gender, time between the initial ACL reconstruction and re-injury, and etiology/mechanism of failure) and surgical factors (graft type, tunnel angle). METHODS: This was a cohort study of 60 patients that underwent revision ACL surgery after previous single-bundle ACL reconstruction. Three sports medicine–trained orthopedic surgeons reviewed the arthroscopic videos and determined the rupture pattern of the grafts. The rupture pattern was then correlated to the above-mentioned factors. RESULTS: The inter-observer agreement had a kappa of 0.7. The most common rupture pattern after previous single-bundle ACL reconstruction is elongation of the graft. This is different from the native ACL, which displays more proximal ruptures. With the use of autograft tissue and after a longer period of time, the rupture pattern in revision surgery is more similar to that of the native ACL. CONCLUSION: The most common rupture pattern after previous single-bundle reconstruction was elongation of the graft. Factors that influenced the rupture pattern were months between ACL reconstruction and re-injury and graft type. LEVEL OF EVIDENCE: Cohort study, Level IV.